Aspects of the reproductive ecology of trachycephalus cunauaru (Anura: Hylidae) in the southern amazon - de NORONHA, Janaina da Costa; Prado, Cynthia P. A. [UNESP]; Hero, Jean-Marc; Castley, Guy; Rodrigues, Domingos de Jesus (FapUNIFESP (SciELO), 2021)
Trachycephalus cunauaru is an Amazonian hylid that uses phytotelmata to reproduce. There is relatively little information about the species, mainly due to the difficulty of accessing their reproductive sites. In this study, we gathered data on the ecology and natural history of T. cunauaru in the southern Amazon, in the state of Mato Grosso, Brazil. In addition to natural phytotelmata, we used buckets installed at a height of 10 m as artificial phytotelmata. We compared physical and chemical characteristics, as well as the presence of tadpoles between natural and artificial phytotelmata. We also collected data on the reproductive behavior of the species through the use of camera traps. We recorded a density of 14.1 reproductive sites per km². Environmental parameters differed significantly between artificial and natural phytotelmata. In artificial sites, the presence of tadpoles was directly related to trees with a larger diameter. We registered oophagy for the first time for the species and observed that males can use more than one phytotelm. We also recorded the presence of snakes within the reproductive sites. We determined that artificial sites and digital camera traps are a satisfactory alternative for behavioral observations of T. cunauaru and possibly for other species with a similar habit.
Aspectos da ecologia reprodutiva de trachycephalus cunauaru (Anura: hylidae) na amazônia meridional
Keywords: Amphibians; Artificial reproductive sites; Canopy sampling; Oophagy; Phytotelmata